2015
DOI: 10.18632/oncotarget.4546
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of FOXM1 overexpression in epithelial ovarian cancer and functional contribution to cell cycle progression

Abstract: The FOXM1 transcription factor network is frequently activated in high-grade serous ovarian cancer (HGSOC), the most common and lethal subtype of epithelial ovarian cancer (EOC). We used primary human EOC tissues, HGSOC cell lines, mouse and human ovarian surface epithelial (OSE) cells, and a murine transgenic ovarian cancer model to investigate genetic determinants of FOXM1 overexpression in EOC, and to begin to define its functional contribution to disease pathology. The Cancer Genome Atlas (TCGA) data indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 64 publications
(83 reference statements)
8
88
0
Order By: Relevance
“…A subsequent study [6] compared 47 cell line molecular profiles to the TCGA data and suggested that the most highly cited cell lines in research papers investigating HGSOC are not the cell lines most likely to actually represent HGSOC. Specifically, out of 47 cell lines used in the analysis, the two most highly cited - SKOV3 and A2780 - had some of the lowest suitability scores for HGSOC and were therefore ranked as “unlikely high grade serous.” A number of the cell lines listed as “likely high-grade serous” in this study have had this status confirmed in other studies using a variety of metrics [5, 7, 9]. Angleiso et al reported a set of molecular features and biomarkers in a panel of ovarian cancer cells establishing their histotype [5].…”
Section: Introductionsupporting
confidence: 77%
“…A subsequent study [6] compared 47 cell line molecular profiles to the TCGA data and suggested that the most highly cited cell lines in research papers investigating HGSOC are not the cell lines most likely to actually represent HGSOC. Specifically, out of 47 cell lines used in the analysis, the two most highly cited - SKOV3 and A2780 - had some of the lowest suitability scores for HGSOC and were therefore ranked as “unlikely high grade serous.” A number of the cell lines listed as “likely high-grade serous” in this study have had this status confirmed in other studies using a variety of metrics [5, 7, 9]. Angleiso et al reported a set of molecular features and biomarkers in a panel of ovarian cancer cells establishing their histotype [5].…”
Section: Introductionsupporting
confidence: 77%
“…CNA are the predominant molecular alteration in HGSC and are associated with altered gene expression [4, 38, 39]. The chromosomal location of PRAME is 22q11.22.…”
Section: Resultsmentioning
confidence: 99%
“…RAB25, a small GTPase, is amplified and upregulated in many ovarian carcinomas and regulates motility, aggressiveness, apoptosis and autophagy (147). Expression of forkhead box M1 (FOXM1), a transcription factor, correlates with poor prognosis as assessed by immunohistochemistry in 158 patients with ovarian carcinoma (148). FOXM1 induces ovarian cancer cell proliferation and migration of HO-8910 ovarian cancer cells, as well as expression of MMP2, MMP9 and VEGFA (148).…”
Section: Fatty Acid Synthase (Fasn) and Fatty-acid Binding Protein 4 mentioning
confidence: 99%